Dinamika Urbanisasi di Provinsi Kalimantan Timur - Puspita Dewi, Dhyah; Adhar, Khairunnisa (Perencanaan Wilayah dan Kota, Institut Teknologi Kalimantan, 2024)
Urbanization is an unavoidable phenomenon that continues to occur today. The process of urbanization in Indonesia has been ongoing since its independence and continues to this day. East Kalimantan Province is one of the main destinations for urbanization. This study aims to identify the dynamics of urbanization in East Kalimantan Province. Secondary data, such as population censuses and Google Earth imagery from 2020, 2010, and 2000, were analyzed quantitatively and qualitatively, and presented descriptively. The results of the study indicate that the level of urbanization in East Kalimantan varies significantly, with its peak reaching 100% in Balikpapan City and Bontang City, reflecting the disappearance of rural areas. The highest population concentrations were found in Samarinda City and Balikpapan City. This study is expected to serve as a basis for stakeholders in policy-making to harness the positive impacts of urbanization and minimize its significant negative impacts.